Acupuncture treatment vs. cognitive rehabilitation for post-stroke cognitive impairment: A systematic review and meta-analysis of randomized controlled trials - Liu, Yang; Chen, Fuyan; Qin, Peng; Zhao, Lu; Li, Xingping; Han, Jiangqin; Ke, Zi; Zhu, Honghang; Wu, Bangqi (Frontiers in Neurology, 2023)
Background: Cognitive impairment is one of the common sequelae after stroke, which not only hinders the recovery of patients but also increases the financial burden on families. In the absence of effective therapeutic measures, acupuncture has been widely used in China to treat post-stroke cognitive impairment (PSCI), but the specific efficacy is unclear. Therefore, this review aimed to evaluate the true efficacy of acupuncture treatment in patients with PSCI. Methods: We searched eight databases [Pubmed, Embase, Web of Science, Cochrane Central Register of Controlled Trials, China Biomedical Literature Database (CBM), China Science and Technology Journal (VIP) database, the China National Knowledge Infrastructure (CNKI) database, and Wan fang database] from the inception to May 2022 for randomized controlled trials (RCTs) related to acupuncture for PSCI. Two investigators independently used a pre-designed form to extract valid data from eligible RCTs. The risk of bias was assessed through tools provided by the Cochrane Collaboration. The meta-analysis was implemented through Rev Man software (version 5.4). Results: Thirty-eight studies involving a total of 2971 participants were included in this meta-analysis. Overall, the RCTs included in this meta-analysis were poor in methodological quality. The combined results showed that acupuncture treatment combined with cognitive rehabilitation (CR) showed significant superiority compared to CR alone in terms of improving cognitive function [Mean Difference (MD)=3.94, 95% confidence intervals (CI): 3.16-4.72, P < 0.00001 (MMSE); MD=3.30, 95%CI: 2.53-4.07, P < 0.00001 (MoCA); MD=9.53, 95%CI: 5.61-13.45, P < 0.00001 (LOTCA)]. Furthermore, the combination of acupuncture treatment and CR significantly improved patients’ self-care ability compared to CR alone [MD=8.54, 95%CI: 5.42-11.66, P < 0.00001 (MBI); MD=5.24, 95%CI: 3.90-6.57, P < 0.00001 (FIM)]. The subgroup analysis based on acupuncture types showed that electro-acupuncture did not show sufficient advantages compared to CR alone (MD=4.07, 95%CI: -0.45-8.60, P = 0.08). Conclusion: This review found that acupuncture treatment may have a positive effect on improving cognitive function and self-care ability in PSCI patients. However, our findings should be treated with caution owing to the existence of methodological quality issues. High-quality studies are urgently required to validate our results in the future.